Revision of the genus Xanthopimpla Saussure (Hymenoptera: Ichneumonidae: Pimplinae) in Vietnam, with descriptions of fourteen new species - Pham, Nhi Thi; Broad, Gavin R.; Matsumoto, Rikio; Wägele, Wolfgang J. (Zootaxa, 2011)
The Vietnamese species of the large, tropical genus Xanthopimpla Saussure, 1892 are revised for the first time. Of a total fauna of 60 species, 14 species are described as new: X. amplamaculosa sp. nov., X. boehmei sp. nov., X. chiuae sp. nov., X. flavafemora sp. nov., X. flavapropodea sp. nov., X. hienae sp. nov., X. morsei sp. nov., X. omega sp. nov., X. oriole sp. nov., X. panthera sp. nov., X. porrecta sp. nov., X. punctatissima sp. nov., and X. spicula sp. nov. Seventeen species are newly recorded from Vietnam: X. annulata Cushman, X. atriclunis Townes & Chiu, X. brachycentra Krieger, X. brevicarina Wang, X. connexa Krieger, X. curvimaculata (Cameron), X. fastigiata Krieger, X. glaberrima Roman, X. jacobsoni Krieger, X. melanacantha Krieger, X. nigritarsis Cameron, X. platyura Townes & Chiu, X. pleuroschista Townes & Chiu, X. pulvinaris Townes & Chiu, X. sexlineata Cameron, X. stricta Townes & Chiu, and X. transmaculata Wang & Huang. The following synonymies are proposed: Xanthopimpla clivulus Townes & Chiu, 1970 = Xanthopimpla clivulus indica Townes & Chiu, 1970, syn. nov., = X. clivulus indicata Gupta, 1987, syn. nov.; Xanthopimpla curvimaculata (Cameron, 1899) = X. curvimaculata pendleburyi Townes & Chiu, 1970, syn. nov.; Xanthopimpla despinosa despinosa Krieger, 1915 = X. despinosa leipepheles Townes & Chiu, 1970, syn. nov. = X. despinosa subquadrata, syn. nov.; Xanthopimpla elegans elegans (Vollenhoven, 1879) = X. elegans apicipennis (Cameron), syn. nov.; Xanthopimpla melanacantha melanacantha Krieger, 1914 = X. melanacantha oblongata Chao, 1997, syn. nov., = X. melanacantha subtriangulata Chao, 1997, syn. nov.; Xanthopimpla nana nana Schulz, 1906 = X. nana aequabilis Townes & Chiu, 1970, syn. nov. = X. nana bravisulcus Wang, 1987, syn. nov. A key to the Vietnamese Xanthopimpla is provided.